Public organizational materiality: A study of physical organization and social interaction in local health houses - Østergaard-Møller, Marie; Elmholdt, Kasper (Politica, 2018)
This article examines how the public organizational materiality of local health houses forms the social interaction of citizens with the health house, each other and the professionals. The establishment of local health houses provides a unique opportunity to study the importance of an organization’s physical framework for the encounter between citizens and the public. The article is based on 22 citizen interviews and on-site observations of physical frameworks, organization of service and social interactions in 19 health houses. We show how the organization of receptions, the use of information objects and the interior design of health houses affect the citizens’ social interaction in the health houses and their expectations to the meeting with the public in a concrete physical context. We find that the “locally based health services” invite citizens to more or less ritualized behavior depending on the physical and organizational framework. The article is based on a database and observation data, which are relatively rare in political science and public administration studies, and contributes to revitalizing the relatively limited micro-sociological literature of the importance of physical frameworks for public organization and management.